Modeling and forecasting of international tourism demand in ASEAN countries - Karimi, Asrin; Faroughi, Pouya; Abdul Rahim, Khalid (Science Publications, 2015)
This study attempts to find the best model to forecast international tourism demand using a series of key macroeconomic variables in ASEAN countries. Generally, we find that generalized Poisson regression model is the best one for estimating long-run international tourism demand. In addition, we find that inflation and real exchange rate have negative relationship with international tourism demand. On the other hand, foreign direct investment and openness of trade have positive relationship with international tourism demand. Cointegration test result shows that there is a long-run relationship between variables.